Dynamic Kinetic Resolution of Phosphinic Acid Derivatives via Nucleophilic Substitution at Phosphorus Center - Strzelecka, Dorota; Bąk, Olga; Borowski, Piotr; Stankevič, Marek (Synthesis, 2018)
Reaction of racemic phosphinic acid derivatives with chiral alcohols proceeds with predominant formation of one diastereomer. The highest level of enrichment has been obtained for transesterfication of racemic methyl benzylphenylphosphinate (64% de). The outcome of the reaction depends on both the structure of chiral alcohol and the starting organophosphorus compound. The results strongly suggest that the nature of the observed phenomena is not a classical equilibration of intermediates found in dynamic kinetic resolution process but is a result of a different reactivity of both enantiomers of racemic substrate towards the same chiral nucleophile.
Keywords: phosphinic acid derivatives; transesterification; dynamic kinetic resolution; Berry pseudorotation; stereochemistry